Intervention of a specific professional competence of the educational field in the physical education class in secondary education (Revista horizonte, 2011)
Objetive: make a diagnostic of professional competencies in physical education teachers, relative to design, development and evaluation of the learning process in education centres in Osorno city. Methods: this investigation uses a qualitative approach, with a modality of collaborative-action, present by an intervention of competencies in physical education teachers. The selected teachers work in schools of different dependency (public, private), of medium socioeconomic class. The sample was no probabilistic, because the teachers must accept been watched during the intervened classroom. The teachers were watched during 4 consecutive classrooms. Results: the planning and evaluation of classes do not change significantly, but the development of this does change (the teacher’s worries more for the learning of the students. CONCLUSION: the development of classroom improves. Also, the structure of classrooms is changed by the teacher, which make more easy seen the different parts of this (beginning, development, ending); this increased the motivation of the students